The Influence of the Canva Application in Improving Primary School Student Achievement in West Sumatra - Rinovian Rais; Ira Zulfa (Journal of Social Science Utilizing Technology, 2024)
Background. The use of media in education is becoming increasingly important, especially in the current digital era. The Canva application has become a popular tool among teachers for creating interesting and informative learning materials. With a variety of visual features and ease of use, Canva allows teachers to create learning materials that suit students’ needs. Purpose. The purpose of this research is to evaluate the influence of the Canva application in improving elementary school student achievement in West Sumatra and to understand teachers’ perceptions of its use Canva in learning. Method. This research uses a quantitative survey via Google Form which is distributed via WhatsApp groups to PGSD students in West Sumatra who use Canva as a learning medium. Research ethics were maintained by ensuring data confidentiality and voluntary participation. A total of 30 respondents. Results. This study explores the influence of the Canva application in improving the achievement of elementary school students in West Sumatra by collecting data from 30 respondents and six questions. From the analysis results, the majority of respondents actively use Canva as a learning medium, with most using this application every day or several times a week. The results of the analysis also show that the use of Canva in learning is considered effective in improving students’ understanding of learning materials, with the majority of respondents reporting an increase in student achievement after using learning materials created with Canva. Conclusion. Canva positively impacts elementary student achievement in West Sumatra by offering an intuitive user experience for teachers, enhancing student understanding, and boosting overall learning quality. It’s recommended to fellow teachers as an effective tool.